Peningkatan Motivasi Belajar Peserta Didik Melalui Strategi Index Card Match pada Pembelajaran PAI di SMKN 1 Ponorogo - Ririn Nuraini (Institut Agama Islam Riyadlotul Mujahidin Ngabar Ponorogo, 2022)
Learning is an activity that is always in touch with students. Related to the learning process until now, the learning motivation of students is one component that still needs to be considered. In this case, learning motivation is an important aspect as a supporter of the success of the learning process. This article aims to explain the implementation of the index card match strategy in PAI learning at SMKN 1 Ponorogo. This research is motivated by the phenomenon that the world of education is still faced with low learning motivation of students which will have implications for student achievement. Therefore, educators need creativity in creating a pleasant learning atmosphere. One of the efforts made is to implement the index card match learning strategy. The approach used in this research is a qualitative approach and the type of research is a case study. With data collection procedures using: in-depth interviews, non-participatory observation and documentation. The data analysis used is the Miles and Huberman interactive model data analysis, which includes: data collection, data reduction, data presentation, as well as drawing conclusions and verification. The results of this study indicate that the application of the index card match strategy has a positive impact on the learning motivation of students at SMKN 1 Ponorogo, especially in PAI learning. Among them are students become more active and enthusiastic in the learning process, students are more confident and enthusiastic than before, learning motivation and learning achievement are increasing and train children to think critically in dealing with problems in the PAI learning process.